Snail and the whale - Donaldson, Julia; Scheffler, Axel (ill.) (London Macmillan, 2015)
The sea snail slithered all over the rock and gazed at the sea and the ships in the dock. And as she gazed she sniffed and sighed. "The sea is deep and the world is wide! How I long to sail!' said the tiny snail.
Contains colourful illustrations
Keywords: Children-Story